Upaya Penyelesaian Kasus Kecelakaan Lalu Lintas Di Wilayah Hukum Kepolisian Daerah Jawa Timur - Khofifah Diva Oktakinanti; Anggrita Esthi (DE RECHT (Journal of Police and Law Enforcement), 2024)
Traffic accident cases constitute a complex legal matter, as they encompass two distinct forms of criminal liability, namely intentional wrongdoing and negligence, each carrying different legal consequences. In Indonesian law enforcement practice, the resolution of such cases has not followed a uniform pattern, given that two primary mechanisms are available: formal litigation under Article 310 of the Traffic and Road Transport Law and Article 359 of the Criminal Code, and restorative justice as governed by Police Regulation No. 8 of 2021. This study aims to examine the implementation of both mechanisms and their relevance to the foundational legal values of justice, utility, and legal certainty. The research employs an empirical legal method with a socio-legal approach, conducted through in-depth interviews with investigators from the East Java Regional Police, field observation, and documentary analysis encompassing court decisions and applicable legislation. The findings reveal that over 90 percent of traffic accident cases within the East Java Regional Police jurisdiction in 2023 and 2024 were resolved through restorative justice by means of SP3 issuance, while cases involving fatalities continued to be processed through formal litigation, as reflected in the Jombang District Court Decision No. 152/Pid.Sus/2024. This study concludes that both mechanisms are complementary in nature and must be operationalized in a coordinated manner to achieve law enforcement outcomes that are equitable for all parties concerned.